(untitled) (Eurasian Journal of Religious Studies, 2018)
In the article from the point of view of ethnography questions of genesis, peculiarities of everyday life, traditional occupations, mentality, rituals, religious beliefs of Dungan are considered. The debatable ethnonym «Dungane» is characterized. Reliance is made on the works of pre-revolutionary researchers (VP Vasiliev, VF Poyarkov), as well as Soviet (GG Stratanovich, NN Cheboksarov, Kh.Yu. Yusurov, M.Ya. Sushanlo) and modern Dunganists (OI Zavyalova, M.Kh. Imazov). Such scientific methods as historical analysis, classification, analogy, statistical sampling are used. The focus is on the position of the Dungan in Kazakhstan: confessional identity, the role of public associations, the preservation of traditions and national mentality in the modern world, and participation in the dialogue of cultures. The aim of the research is to reveal the connection between the modern state of the Dungan and their complex ethnogenesis and a unique set of traditions. Conclusions are drawn that the people are characterized by a historically formed and rooted in its mentality of tolerance, the role of the Dungan Association, the Dungan newspaper Huiming Bo, the Kazakh Donggang Society in modern processes. Highly urgent problems are identified, such as: the preservation of an original culture, traditions, language, the need for Dungan-speaking education programs, the support of state structures in the organization of schools, children’s institutions with a national language of instruction, with special strategies for preserving the traditional heritage.